Computer aided systems theory – EUROCAST 2017. 16th International Conference, Las Palmas de Gran Canaria, Spain, February 19-24, 2017, Revised selected papers /: 16th International Conference, Las Palmas de Gran Canaria, Spain, February 19-24, 2017, Revised selected papers. Part I : (2018) - Unknown
No abstract available